2018
DOI: 10.1128/aac.02213-17
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Persistent Burkholderia cepacia Complex Bacteremia with Ceftazidime-Avibactam

Abstract: We report our clinical experience treating a 2-month-old infant with congenital diaphragmatic hernia who experienced prolonged bacteremia with complex (Bcc) despite conventional antibiotic therapy and appropriate source control measures. The infection resolved after initiation of ceftazidime-avibactam. Whole-genome sequencing revealed that the isolate most closely resembled and identified the mechanism of resistance that likely contributed to clinical cure with this agent. Ceftazidime-avibactam should be consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 14 publications
0
24
0
4
Order By: Relevance
“…34 A case report of persistent BCC bacteremia in a 2-month-old infant was cleared with ceftazidime-avibactam. 35 Due to limited in vivo evidence, treatment of BCC is largely driven by in vitro data and individual susceptibilities. Therefore, trimethoprimsulfamethoxazole, meropenem, and ceftazidime are first-line agents (Table 6).…”
Section: Clinical Treatment Datamentioning
confidence: 99%
See 1 more Smart Citation
“…34 A case report of persistent BCC bacteremia in a 2-month-old infant was cleared with ceftazidime-avibactam. 35 Due to limited in vivo evidence, treatment of BCC is largely driven by in vitro data and individual susceptibilities. Therefore, trimethoprimsulfamethoxazole, meropenem, and ceftazidime are first-line agents (Table 6).…”
Section: Clinical Treatment Datamentioning
confidence: 99%
“…64 Due to limited clinical treatment data, literature analyzing in vitro susceptibilities of Achromobacter and Alcaligenes suggests that piperacillin-tazobactam, carbapenems, ceftazidime, or trimethoprim- Trimethoprim-sulfamethoxazole Minocycline Levofloxacin Tigecycline Ceftazidime-avibactam + aztreonam Amoxicillin-clavulanate + aztreonam Burkholderia cepacia complex 2,17,[19][20][21][22][23][24][25][26] Trimethoprim-sulfamethoxazole Meropenem Ceftazidime Minocycline Ceftazidime-avibactam Ceftazidime-avibactam + piperacillin-tazobactam Elizabethkingia spp. 27,30,[35][36][37][38] Combination of any of the below: Minocycline Moxifloxacin, levofloxacin Rifampin Piperacillin-tazobactam Trimethoprim-sulfamethoxazole…”
Section: Clinical Treatment Datamentioning
confidence: 99%
“…While there are limited data on the treatment of trimethoprim-sulfamethoxazole-resistant B. cepacia complex, recent anecdotal evidence has suggested that ceftazidime-avibactam may be used successfully. 132 One new drug that may be beneficial for the treatment of drug-resistant S. maltophilia and Burkholderia species includes cefiderocol. 133 As previously noted, cefiderocol is a cephalosporin conjugated with a catechol siderophore and in vitro studies have shown activity against S. maltophilia and Burkholderia species, but once again, additional clinical data are awaited before it can be recommended for use.…”
Section: Mdr-acinetobacter Baumanniimentioning
confidence: 99%
“…Based on the results from these trials, the Food and Drug Administration (FDA) has recently approved its use in pediatric patients Ͼ3 months of age with complicated intra-abdominal infections (cIAIs), in conjunction with an agent active against anaerobic organisms, and also those with urinary tract infections (UTIs). Currently, clinical data on the treatment of CRE infections with ceftazidime-avibactam in the pediatric population are limited to a few case reports (32,(75)(76)(77)(78).…”
Section: Treatmentmentioning
confidence: 99%